Vulnerability of families with children with intestinal stomas - Clara Ferraz Lazarini Zacarin; Willyane de Andrade Alvarenga; Renata Olzon Dionísio de Souza; Daianne Cibele de Souza Borges; Giselle Dupas (Universidade Federal de Goias, 2014)
Intestinal stomas cause transformations in the body and create specific and continuous needs for care that imply in hospitalization and surgeries. In this context, we applied the concept of family vulnerability in order to identify the vulnerability of the family living with a child who has intestinal stoma. It is a qualitative study which interviewed the mothers of children with this chronic condition. We used narrative analysis based on the concept of family vulnerability. The results display that the family has gone through previous noteworthy experiences associated with the child's condition. The family cares for the child on their own and seeks ways to control the situation and regain autonomy, hoping for stoma reversal. Based on the concept of vulnerability, we observed that these families can be considered vulnerable, for they experience threats to their autonomy, but are moved by the hope of reversal and intestinal tract reconstruction. doi: 10.5216/ree.v16i2.26639.